Metamizole: An underrated agent causing severe idiosyncratic drug‐induced liver injury. Issue 7 (3rd March 2020) - Sebode, Marcial; Reike‐Kunze, Martin; Weidemann, Sören; Zenouzi, Roman; Hartl, Johannes; Peiseler, Moritz; Liwinski, Timur; Schulz, Lisa; Weiler‐Normann, Christina; Sterneck, Martina; Lohse, Ansgar W.; Schramm, Christoph
Abstract : Aims: Drug‐induced liver injury (DILI) is a heterogenous entity leading to liver damage. We have analysed the frequency, biochemical and histological patterns and clinical courses of DILI cases due to metamizole at our tertiary care centre in Hamburg, Germany. Methods: Consecutive patients with DILI who presented to our clinic were analysed retrospectively. Causes of acute hepatitis other than DILI were excluded. Results: In total, 154 DILI cases were admitted to our centre from 2008 to 2017. After phenprocoumon, metamizole was the second most frequent putative agent causing DILI (23 of all 154 DILI cases, 14, 9%). The biochemical pattern on admission of metamizole‐induced DILI cases was hepatocellular with median levels of alanine transaminase (779 U/L, 64–3532 U/L) by far exceeding median alkaline phosphatase levels (131 U/L, 42–578 U/L). In 17 of the 23 cases (74%) liver biopsy was performed. Moderate to severe inflammatory histological activity and severe centrilobular necrosis (>30%) was present in 76.5 and 35.3%, respectively. Metamizole was involved in 2 DILI cases progressing to acute liver failure, then receiving liver transplantation and still alive at time of assessment. Our data were supported by re‐exposure in 4 patients. Furthermore, a database search for metamizole‐induced liver injury in the European Medicines Agency's database identified about 300 reports on suspected metamizole‐induced DILI in Europe. Conclusion: Elevation of liver enzymes or acute liver failure are not mentioned in the German drug label of metamizole as potential side effects. Our study reveals that in Germany and Europe, metamizole is a frequent and underrated agent causing DILI.